Principal's leadership in improving student learning outcomes - Firdaus, Firdaus; Giatman, Muhammad; Ernawati, Ernawati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this research was to identify, explain, and analyze the principal's of headmasters learning as a step in improving student learning outcomes. The method used is a literature study method with a conceptual research approach related to ideas and theories. Principal leadership in improving student learning outcomes is the most important element in improving the quality of education. In order to be able to improve the quality of education, school principals must do good learning in their leadership. Based on the instructional leadership model expressed by Weber dan Murphy, it can be concluded that good instructional leadership must include activities including, developing the school's vision, mission, and goals, developing learning programs that can meet needs, developing an academic learning climate, creating a work environment that is conducive to learning. support and implement comprehensive learning assessments. Principal instructional leadership is a multidimensional construct that focuses on how principals organize and perform coordination tasks in school life. In creating effective learning lead ership a synergistic relationship is needed with all school members.